Optimizing Social Work and Restorative Justice In Overcoming Overcrowded Correctional Institutions - Budi Prayogo, Sutras; Asyahadi, Farhan; Abas, Muhamad (Dinasti Research, 2024)
The legal culture of society in Indonesia assumes that providing sanctions or punishment for perpetrators of crimes until they are sent to detention is the easiest method and provides satisfaction for the victim. Crime itself is a social control institution that is linked to and always reflects the values and structure of society, so that it is a symbolic reaffirmation of violations of the collective conscience. In the view of researchers, restorative justice and human rights are one unit because it is law that embodies human rights values. We must ensure that the orientation regarding corrections must of course be in line with the conceptual change in the goals of corrections from the concept of retribution towards the concept of rehabilitation.